JALAME RESTUDIED AND REINTERPRETED - Warner Slane, Kathleen; Magness, Jodi (Rei Cretariae Romanae Fautorum Acta, 2024)
Jalame is a rural site in Israel a few kilometers southeast of Haifa. It was chosen by Gladys Weinberg and Paul Perrot from among a number of sites surveyed as the most likely location of a Roman glass factory. Excavated by the University of Missouri and the Corning Museum of Glass between 1964 and 1967, it was at that time one of a handful of stratigraphically excavated Roman sites in the East. At the time of the excavation LR fine wares in the East could be subdivided by fabric but were still dated “late 4th – 6th cent.”. The chronology of the site was therefore estab- lished on the basis of the identifiable coins: the main period of the villa with its wine and oil presses was dated before 350 AD, the glass furnace and its associated dumps and sorting floors between 351 and 378 AD, and a single later phase of the villa was dated 383–408 AD.